A thousand acres - Smiley, Jane. (New York : Ballantine Books, 1992)
A successful Iowa farmer decides to divide his farm between his three daughters. When the youngest objects, she is cut out of his will. This sets off a chain of events that brings dark truths to light and explodes long- suppressed emotions. An ambitious reimagining of Shakespeares King Lear cast upon a typical American community in the late twentieth century, A Thousand Acres takes on themes of truth, justice, love, and pride, and reveals the beautiful yet treacherous topography of humanity.
"A Fawcett Columbine book."
Accelerated Reader AR
Keywords: Family farms -- Fiction; Iowa -- Fiction; Allegories